Low-cost and easy-to-form silicon-based epitaxial magneto-optical film as well as preparation method and application thereof

By wrapping ZnFe2O4 nanoparticles with ZIF-8 frame structure on a silicon base, and evenly dispersing them in the ultraviolet glue through PgC5Cu bridge agent, the lattice mismatch and complex preparation process problems when integrating magneto-optical materials on a silicon base are solved, and a low-cost, easy-to-form silicon-based epitaxial magneto-optical film is achieved, with excellent magneto-optical performance and optical transparency.

CN119902389AActive Publication Date: 2025-04-29FUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510320435.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-29
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

When integrating magneto-optical materials on silicon, problems such as lattice mismatch and mismatch of thermal expansion coefficients are often encountered, resulting in poor material quality and device performance, and at the same time, the preparation process is complex and the cost is high.

Method used

ZnFe2O4 nanoparticles were wrapped with ZIF-8 frame structure, and PgC5Cu metal organic nanocapsules were used as a bridge agent to disperse the nanoparticles evenly in the ultraviolet light glue, and a silicon-based epitaxial magneto-optical film was prepared by ultraviolet curing.

Benefits of technology

The uniform dispersion of nanoparticles with strong magneto-optical effects has been achieved, which reduces production costs and cycles, improves the optical transparency and magnetic properties of the materials, and is suitable for optical fiber communications, integrated optical devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119902389A_ABST
    Figure CN119902389A_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost and easy-to-form silicon-based epitaxial magneto-optical thin film and a preparation method and application thereof, ZnFe2O4 nanoparticles which have a strong magneto-optical effect but are easy to agglomerate are uniformly dispersed in ZIF-8 with fixed pores by adopting an in-situ symbiosis technology, and PgC5Cu is used as a bridging agent to modify the surface of the ZIF-8, so that the silicon-based epitaxial magneto-optical thin film is obtained. And then uniformly dispersing in ultraviolet light glue to prepare a glue solution, uniformly coating a silicon substrate with the obtained glue solution, and successfully constructing the silicon-based epitaxial thin film material with excellent magneto-optical characteristics through ultraviolet curing. The preparation method is relatively simple and convenient and high in operability, the prepared film material is outstanding in magneto-optical performance and shows good application potential in various fields such as magneto-optical storage, magneto-optical sensors, photoelectric integration and micro-nano optical devices, and a novel material with great value is provided for magneto-optical film research and device development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optoelectronic information materials, and in particular relates to a low-cost, easily formed silicon-based epitaxial magneto-optical film and a preparation method and application thereof. Background Art

[0002] With the development of emerging technologies such as 5G communication, interstellar communication, and big data centers, data networks need to carry massive amounts of information communication and information processing, and high-performance, highly integrated information processing devices are urgently needed. Among them, silicon-based magneto-optical isolators are one of the difficult problems of the next generation of information technology - integrated silicon photonics. For example, in the field of optical communications, in order to achieve high-speed and large-capacity data transmission, devices such as magneto-optical isolators are needed to ensure stable signal transmission, which has promoted the extensive application of silicon-based integrated magneto-optical materials. Common magneto-optical materials integrated on silicon include yttrium iron garnet (YIG) and doped yttrium iron garnet, bismuth-doped rare earth iron garnet (Bi:YIG), indium antimonide (InSb), bismuth ferrite (BiFeO3), rare earth iron garnet, etc. Among them, YIG and its doped materials have the characteristics of high Faraday rotation and low loss, and are currently the most widely used magneto-optical materials; Bi:YIG further optimizes the magneto-optical performance by doping with bismuth elements; InSb has a significant magneto-optical effect in the terahertz band; BiFeO3 has unique magneto-electric coupling characteristics and certain magneto-optical effects.

[0003] At present, the commonly used methods for integrating magneto-optical materials on silicon include heteroepitaxial growth, ion implantation, direct bonding, and micro-nano processing. However, in this integration process, due to the significant differences in the physical and chemical properties between magneto-optical materials and silicon-based materials, many problems such as lattice mismatch and thermal expansion coefficient mismatch are often easily caused, which in turn have an adverse effect on material quality and device performance. In addition, the preparation process of integrated magneto-optical materials on silicon is extremely complicated. It not only requires high-precision equipment as support, but also relies on advanced technical means to ensure it, which makes the production cost rise sharply and the production difficulty increase significantly. It is particularly important that when designing integrated optical systems, it is difficult to realize the integration of optical components on a very small scale due to the limitations of the physical properties and processing technology of traditional crystal materials. However, if the magnetic element particle size is prepared to be small enough and highly uniformly dispersed in a transparent polymer, it is expected to obtain a highly transparent and strong magneto-optical material. Summary of the invention

[0004] In view of the problems of long preparation cycle, high cost, difficult molding, difficulty in making heterogeneous devices, and difficulty in optical integration of traditional crystal and glass magneto-optical materials, the present invention provides a low-cost, easy-to-mold silicon-based epitaxial magneto-optical film and its preparation method, which uses the framework structure of ZIF-8 to wrap ZnFe2O4 nanoparticles with strong magneto-optical effect, and then uses PgC5Cu metal organic nanocapsules as a bridge between MOF and polymer to achieve the nanoparticles with strong magneto-optical effect uniformly dispersed in transparent ultraviolet glue, and then ultraviolet curing, so as to realize the epitaxial preparation of magneto-optical film on silicon. The obtained silicon-based epitaxial magneto-optical film is expected to be practically applied in optical fiber communication, integrated optical devices, miniaturization, and new heterogeneous magneto-optical devices.

[0005] To achieve the above object, the present invention adopts the following technical solution: A silicon-based epitaxial magneto-optical film is prepared by firstly using ZIF-8 to wrap ZnFe2O4 nanoparticles, so that the ZnFe2O4 nanoparticles are uniformly dispersed in ZIF-8 with fixed pores to obtain ZnFe2O4-ZIF-8, and then using pentylphthalene copper (PgC5Cu) as a bridging agent to modify the surface of ZIF-8 to obtain ZnFe2O4-ZIF-8@PgC5Cu, which is then dispersed in ultraviolet adhesive (UCA) to prepare an adhesive liquid, and the obtained adhesive liquid is uniformly coated on a silicon substrate and obtained by ultraviolet curing.

[0006] The method for preparing the silicon-based epitaxial magneto-optical film comprises the following steps: 1) Preparation of ZnFe2O4-ZIF-8: FeSO4·7H2O and (CH3COO)2Zn·2H2O were added to deionized water and mixed evenly to obtain solution A; 2-methylimidazole was added to deionized water and mixed evenly to obtain solution B; solution B was quickly poured into solution A, stirred for 30 min, and then transferred to a reactor for reaction. After the reaction, the product was cooled to room temperature, and then washed with water, methanol, and dichloromethane (DCM) three times each to obtain ZnFe2O4-ZIF-8; 2) Preparation of ZnFe2O4-ZIF-8@PgC5Cu: Weigh pentylphthalene copper (PgC5Cu) and prepared ZnFe2O4-ZIF-8 in centrifuge tubes A and B respectively, then add dichloromethane to centrifuge tubes A and B respectively, after PgC5Cu is dissolved, mix the two solutions, ultrasonically react for 3 min, centrifuge, and wash with DCM three times to obtain ZnFe2O4-ZIF-8@PgC5Cu; 3) Preparation of magneto-optical film: The obtained ZnFe2O4-ZIF-8@PgC5Cu is mixed with ultraviolet glue, and after being completely dispersed by ultrasound, the obtained dispersion is coated on a silicon substrate by spin coating or inkjet printing, and the silicon substrate surface is irradiated with an ultraviolet lamp to obtain a silicon-based polymer magneto-optical film with uniform thickness.

[0007] Furthermore, the molar ratio of FeSO4·7H2O, (CH3COO)2Zn·2H2O and 2-methylimidazole used in step 1) is 0.43:0.765:5.5.

[0008] Furthermore, the reaction temperature in step 1) is 120° C. and the reaction time is 2 h.

[0009] Furthermore, the mass ratio of the copper amylphthalene to ZnFe2O4-ZIF-8 used in step 2) is 1:20.

[0010] Furthermore, the UV adhesive in step 3) is prepared by mixing polyurethane acrylate, 1,6-hexanediol diacrylate (HDDA) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 7:2:1.

[0011] Furthermore, in step 3), the mass ratio of ZnFe2O4-ZIF-8@PgC5Cu to the ultraviolet adhesive is 1:50~1:200.

[0012] Furthermore, the coating amount of the dispersion on the silicon substrate in step 3) is 20 μL / cm 2 .

[0013] Furthermore, the power of the ultraviolet lamp used in step 3) is 6 W.

[0014] Furthermore, the irradiation treatment time in step 3) is 10 minutes.

[0015] By utilizing the method for preparing the silicon-based epitaxial magneto-optical film, magneto-optical elements with special shapes can be prepared by using a special-shaped silicon base according to the requirements of special-shaped magneto-optical devices.

[0016] The prepared magneto-optical film or magneto-optical element can be further made into magneto-optical devices, including magneto-optical isolators, miniaturized or integrated optical integrated devices, optical circulators, magneto-optical modulators, magneto-optical memories, etc.

[0017] The present invention proposes for the first time a method for preparing silicon-based epitaxial magneto-optical film, which uses in-situ symbiosis technology to evenly disperse ZnFe2O4 nanoparticles with strong magneto-optical effect but easy to agglomerate in MOF (metal organic framework ZIF-8) with fixed pores, and uses PgC5Cu (a copper complex with a specific configuration) to modify the surface of ZIF-8 so that it is evenly dispersed in ultraviolet light glue, and successfully constructs a composite material with excellent magneto-optical properties. In the field of optical integration, this innovative design shows many significant advantages. On the one hand, it effectively retains the structural stability and optical transparency of the material itself, which provides a basic guarantee for the optical integrated system to maintain precise optical transmission and signal processing. On the other hand, the design gives the material unprecedented flexibility and processability, greatly expanding the feasibility of constructing complex structures and device layouts in optical integration, and creating key conditions for achieving the lightweight, portable and flexible process of magneto-optical devices. Compared with traditional pure inorganic magneto-optical crystals and magneto-optical glass and other materials, the present invention presents many advantages in optical integration applications. From the perspective of preparation technology, the method is simpler, effectively shortens the production cycle, and significantly reduces energy consumption and cost investment, which is of great economic and efficiency significance for large-scale optical integrated manufacturing and industrialization. At the same time, it has the characteristics of easy molding and high flexibility, which makes it more flexible to adapt to various special space restrictions and functional requirements in the design and implementation of optical integration, so that it can widely match different optical integration application scenarios, greatly enriching the potential application value and development potential of optical integration technology in multiple fields.

[0018] The significant advantages of the present invention are: (1) The magneto-optical film prepared by the present invention has an optical transmittance of up to 60% in the 1200-2600 nm band without an anti-reflection film on the film surface.

[0019] (2) The process of preparing the magneto-optical film of the present invention is simple and efficient. It only requires ultraviolet light irradiation and can be directly formed without additional processing steps. It has low preparation cost and short cycle, and exhibits excellent self-assembly performance and material molding convenience. The obtained magneto-optical film exhibits excellent magnetic and optical properties, providing high-performance, low-cost new materials for the fields of magneto-optics, optical integration, etc.

[0020] (3) The preparation method of the present invention can give silicon-based optoelectronic devices more novel functional properties. For example, by utilizing the characteristics of magneto-optical composite materials, it is possible to flexibly control parameters such as the polarization state and intensity of light, develop optical modulators, optical switches and other devices with special functions, enrich the functional types of silicon-based optoelectronic devices, and provide basic support for the development of cutting-edge fields such as optical computing and quantum communication. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the X-ray diffraction spectrum of ZnFe2O4-ZIF-8 prepared in the example.

[0022] Figure 2 VSM spectra of ZnFe2O4-ZIF-8 and ZnFe2O4-ZIF-8@PgC5Cu powders prepared in the examples at room temperature.

[0023] Figure 3 The transmission spectra of the magneto-optical films prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV glue in different mass ratios (1:50, 1:100, 1:200) in the examples.

[0024] Figure 4 This is the VSM spectrum of the magneto-optical film prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV glue in different mass ratios (1:50, 1:100) at room temperature in the example.

[0025] Figure 5 : This is the magnetic circular dichroism spectrum at 200-800 nm of the magneto-optical film prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and ultraviolet glue in different mass ratios (1:50, 1:100, 1:200) in the example. DETAILED DESCRIPTION

[0026] A magneto-optical film prepared by silicon-based epitaxy, the preparation of which comprises the following steps: 1) Preparation of ZnFe2O4-ZIF-8: FeSO4·7H2O and (CH3COO)2Zn·2H2O were added to deionized water and mixed evenly to obtain solution A; 2-methylimidazole was added to deionized water and mixed evenly to obtain solution B; solution B was quickly poured into solution A, stirred for 30 min, and then transferred to a reactor containing a polytetrafluoroethylene liner, heated at 120°C for 2 h, cooled to room temperature, and then the obtained product was washed three times with water, methanol, and dichloromethane (DCM) in turn to obtain ZnFe2O4-ZIF-8, which was sealed with dichloromethane; 2) Preparation of ZnFe2O4-ZIF-8@PgC5Cu: Weigh pentylphthalene copper (PgC5Cu) and prepared ZnFe2O4-ZIF-8 in a mass ratio of 1:20, and place them in centrifuge tubes A and B, respectively. Then, add dichloromethane to centrifuge tube B and mix them by ultrasonication. Add dichloromethane to centrifuge tube A. After PgC5Cu is dissolved, add it to centrifuge tube B. After ultrasonication for 3 min, centrifuge and wash with DCM three times to obtain ZnFe2O4-ZIF-8@PgC5Cu. 3) Preparation of magneto-optical film: The obtained ZnFe2O4-ZIF-8@PgC5Cu was mixed with UV glue at a mass ratio of 1:50-1:200, and after being completely dispersed by ultrasound, the obtained dispersion was coated on the silicon substrate by spin coating or inkjet printing, and the coating amount was 20 μL / cm 2 , and then use ultraviolet lamp (power 6 W) to irradiate the silicon-based surface for 10 minutes to obtain a silicon-based polymer magneto-optical film ZnFe2O4-ZIF-8@PgC5Cu / UCA with uniform thickness.

[0027] Wherein, the molar ratio of FeSO4·7H2O, (CH3COO)2Zn·2H2O and 2-methylimidazole used in step 1) is 0.43:0.765:5.5.

[0028] The UV adhesive in step 2) is prepared by mixing polyurethane acrylate, 1,6-hexanediol diacrylate (HDDA) and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 7:2:1.

[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0030] The amylphthalene copper PgC5Cu used in the examples was synthesized according to the literature (Engineering Plasticization Resistant Gas Separation Membranes Using Metal-Organic Nanocapsules. DOI: 10.1039 / d0sc01498b). Example

[0031] A preparation method of a silicon-based epitaxial magneto-optical film, the specific steps of which are as follows: (1) Preparation of ZnFe2O4-ZIF-8: 0.43 mmol FeSO4·7H2O and 0.765 mmol (CH3COO)2Zn·2H2O were added to 5 mL of deionized water and mixed evenly to obtain solution A; 5.5 mmol 2-methylimidazole (C4H6N2) was added to 10 mL of deionized water and mixed evenly to obtain solution B; the obtained solution B was quickly poured into solution A and stirred for 30 min, then transferred to a reactor containing a polytetrafluoroethylene liner, heated at 120°C for 2 h, cooled to room temperature, and then the obtained product was washed three times with water, methanol, and dichloromethane (DCM) in sequence to obtain ZnFe2O4-ZIF-8, which was sealed with DCM; (2) Preparation of ZnFe2O4-ZIF-8@PgC5Cu: Weigh pentylphthalene copper (PgC5Cu) and prepared ZnFe2O4-ZIF-8 in a mass ratio of 1:20 and place them in centrifuge tubes A and B respectively. Then, add DCM in a mass ratio of 1:10 to centrifuge tube B and mix them by ultrasonication. Add DCM in a mass ratio of 1:5 to centrifuge tube A. After PgC5Cu is dissolved, add it to centrifuge tube B. After ultrasonic reaction for 3 min, centrifuge and wash with DCM 3 times to obtain ZnFe2O4-ZIF-8@PgC5Cu, which is then sealed with DCM. (3) Preparation of magneto-optical film: ZnFe2O4-ZIF-8@PgC5Cu was mixed with UV glue at a mass ratio of 1:50-1:200. After being completely dispersed by ultrasonication, the resulting dispersion was coated on a silicon substrate by spin coating or inkjet printing. The coating amount was 20 μL / cm 2 , and then the silicon-based surface was irradiated with an ultraviolet lamp (power 6 W) for 10 minutes to obtain ZnFe2O4-ZIF-8@PgC5Cu / UCA with uniform thickness.

[0032] The phase of the prepared ZnFe2O4-ZIF-8 was characterized by X-ray diffractometer. Figure 1 .Depend on Figure 1 It can be seen that the XRD spectrum of ZnFe2O4-ZIF-8 has characteristic peaks of ZIF-8 and cubic phase ZnFe2O4, indicating that the material Fe3O4 and ZIF-8 are successfully composited.

[0033] Figure 2 The VSM spectra of the prepared ZnFe2O4-ZIF-8 and ZnFe2O4-ZIF-8@PgC5Cu at room temperature. As shown in the figure, the saturation magnetization of ZnFe2O4-ZIF-8 modified with PgC5Cu is 11 emμ / g, which is 69.23% higher than that of ZnFe2O4-ZIF-8.

[0034] Figure 3 The transmission spectra of magneto-optical films prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV adhesive at different mass ratios (1:50, 1:100, 1:200). As can be seen from the figure, the magneto-optical film prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV adhesive at a mass ratio of 1:200 has an optical transmittance of up to 60% in the 1100~2600 nm band.

[0035] Figure 4The VSM spectra of magneto-optical films prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV adhesive at different mass ratios (1:50, 1:100, 1:200) at room temperature. As can be seen from the figure, after adding ZnFe2O4-ZIF-8@PgC5Cu to UV adhesive, the magnetism of the material changes from the original paramagnetism to ferromagnetism.

[0036] Figure 5 The magnetic circular dichroism spectra of magneto-optical films prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV adhesive at different mass ratios (1:50, 1:100, 1:200) at 200-800 nm. As can be seen from the figure, the ellipticity of the magneto-optical films prepared by mixing ZnFe2O4-ZIF-8@PgC5Cu and UV adhesive at mass ratios of 1:50, 1:100, and 1:200 are -2300 mdeg / cm, -1310.69 mdeg / cm, and -565.93 mdeg / cm, respectively.

[0037] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a silicon-based epitaxial magneto-optical film, characterized in that: First, ZnFe2O4 nanoparticles were wrapped with ZIF-8 to obtain ZnFe2O4-ZIF-8, and then its surface was modified with pentylphthalene copper to obtain ZnFe2O4-ZIF-8@PgC5Cu. The obtained ZnFe2O4-ZIF-8@PgC5Cu was mixed with ultraviolet glue to prepare a glue solution, and the glue solution was evenly coated on a silicon substrate and cured by ultraviolet light to obtain a silicon-based polymer magneto-optical film with uniform thickness.

2. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 1, characterized in that: The preparation of ZnFe2O4-ZIF-8 comprises the following steps: 1) Add FeSO4·7H2O and (CH3COO)2Zn·2H2O into deionized water and mix well to prepare solution A; 2) Add 2-methylimidazole to deionized water and mix well to prepare solution B; 3) Solution B was quickly poured into solution A, and after stirring for 30 min, the mixture was transferred to a reactor for reaction. After the reaction, the mixture was cooled to room temperature, and the obtained product was washed to obtain the product.

3. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 2, characterized in that: The molar ratio of FeSO4·7H2O, (CH3COO)2Zn·2H2O and 2-methylimidazole used is 0.43:0.765:5.

5.

4. The method for preparing a magneto-optical film according to claim 2, characterized in that: The reaction temperature is 120°C and the reaction time is 2 h.

5. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 1, characterized in that: The ZnFe2O4-ZIF-8@PgC5Cu is prepared by mixing pentylphthalene copper and ZnFe2O4-ZIF-8 in a mass ratio of 1:20 in dichloromethane, subjecting the mixture to ultrasonic reaction for 3 minutes, centrifuging and washing.

6. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 1, characterized in that: The mass ratio of ZnFe2O4-ZIF-8@PgC5Cu to ultraviolet adhesive is 1:50-1:200; the ultraviolet adhesive is prepared by mixing polyurethane acrylate, 1,6-hexanediol diacrylate and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 7:2:

1.

7. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 1, characterized in that: The coating amount of the glue on the silicon substrate is 20 μL / cm 2 .

8. The method for preparing a silicon-based epitaxial magneto-optical film according to claim 1, characterized in that: The irradiation time of UV curing was 10 min and the power of UV lamp was 6 W.

9. A silicon-based epitaxial magneto-optical film prepared by the method of claim 1.

10. A magneto-optical device prepared using the silicon-based epitaxial magneto-optical film according to claim 9.

Citation Information

Patent Citations

  • Quick response ultraviolet detector and preparation method

    CN107359217A

  • Preparation method of low-cost and easy-to-form flexible magneto-optical composite material

    CN119529458A

  • HIGHLY ORDERED L10 FePT NANOMAGNETS FOR DATA STORAGE AND MAGNETIC SENSING AND METHOD OF MAKING

    WO2006118677A2